Faktor Penentu Gaya Hidup Halal Generasi Z di Sumatera Utara - Rini Hayati Lubis; Nurul Izzah (Jurnal Ilmiah Ekonomi Islam, 2022)
The increasing number of Muslim populations throughout the world has resulted in an increasing level of demand for halal products. Currently there is a shift in lifestyle towards a halal lifestyle. This phenomenon is growing, especially during the COVID-19 pandemic that has hit the whole world. The pandemic demands that people prioritize health by paying more attention to a healthy and hygienic lifestyle. The application of the halal lifestyle has spread throughout the world, not only in Muslim countries but also non-Muslim countries. Its development can be seen in various sectors such as food, beverage, fashion, pharmaceutical, finance and other sectors. The population of Indonesia, which is the largest Muslim majority, is currently dominated by Generation Z. Generation Z, which tends to be literate in information technology, affects the lifestyle that is applied in everyday life. Several studies have stated that Generation Z has not been fully consistent in implementing a halal lifestyle. In choosing products for consumption, they do not always pay attention to the existence of the product's halal label. This is due to the assumption that products produced by Muslims are guaranteed to be halal without having to be accompanied by a halal label on the product. The purpose of this study is to determine the determinants that influence the halal lifestyle of Generation Z in North Sumatra. This study is a quantitative study using primary data obtained by distributing online questionnaires. The number of respondents as many as 445 who are Generation Z in North Sumatra. Research data is processed using Smart PLS. The results showed that the variables of experience, personality, perception, motives and culture influenced the halal lifestyle. Meanwhile, family factors, social environment, and demographics do not affect the lifestyle of Generation Z in North Sumatra. The halal industry needs to continue to be developed to provide Muslim consumers with more diverse choices in determining the products and services to be consumed.